FIT ASSESSMENT IN GARMENT CHOICES AND USAGE OF UNIVERSITIES’ STUDENTS: PERCEIVED CONSEQUENCES FOR WELL BEING - Juliana Ego Azonuche; Blessed Ufuoma Agofure, Ochuko Odogu, Clara Onome Numga, Victoria Igbuwe, Essien Ndarake Aniema Owho (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
The study assessed fit garment choices and usage of universities’ students: perceived consequences for well being. Two research questions and a null hypothesis guided the study. Study area was Delta state and 34,142 students constitute the population from all the seven public universities in the state. Through multi-stage sampling, two universities each (federal and state) were randomly selected. Then proportionate sampling was used to select 335 subjects and 9 users model were purposively selected. Structured questionnaire was used to collect the data; mean, standard deviation and Analysis of Variance (ANOVA) were used for data analyses. Findings showed poor fit on students garment choices and usage viz; neckline sagging, shoulder not hanging smoothly, garment loose/sag at hip, above knee length, no ease in garment, usability and overall fit of garment when sitting, standing and in motion and these have negative consequences such as low self esteem, indecent appearance, lack of self confidence, sexual harassment among others on students well being. The small, medium, and large size-based students (users) did not significantly differ in their responses on 19 items on the fit requirements of the garments but, significantly differed on 17 items. Conclusively, well fitted garments enhance students’ self esteem, body image, self confidence, comfort and daily activities. Therefore, orientation on dress sense will help ensure decent garment choices and usage among student in the universities in Nigeria.